Tantangan dan Realisasi Intelijen dan Keamanan Nasional pada Era 5 - Arbani, Muhammad (Sahabat Publikasi, 2024)
In the wake of Society 5.0 phenomenon this article delves into the intricate interplay between technological progress and national security. Society 5.0 envisions a world where technological innovations, including IoT, Artificial Intelligence, Big Data, and robotics, are harnessed to enhance the fabric of societal life including in national security. While promising unprecedented positive developments particularly in national security and intelligence, this paradigm shift also unfurls a double-edged sword, presenting unforeseen challenges. The era's impact on security and intelligence encompasses increased data connectivity and sharing, paving the way for advanced intelligence technologies such as AI and IoT, and predictive analytics. However, these positive strides are juxtaposed against contemporary challenges that demand practical solutions, commitment, and ample resources. The article meticulously navigates through the labyrinth of these challenges, emphasizing the need for a holistic approach. It unfolds in three parts: exploring the challenges of intelligence and national security in the Society 5.0 era, understanding these challenges to shift towards discussing implementation of intelligence measures in this era to safeguard national security, and finally, culminating in a conclusion that underscores the necessity of commitment, resources, and robust cross-sector collaboration to effectively leverage the positive potential of Society 5.0 in securing nations against present and future security challenges.